Mental health promotion needs assessment of factory workers at a sugar mill company in Swaziland - Manana, Sifiso (My University, 2017)
Background: Work is both an important resource for mental health, yet it also presents psychosocial risks for mental health. The workplace has been identified as a potential setting for both mental health promotion and mental illness prevention. It is well documented in the literature that mental (emotional) health needs of employees should be addressed and a mental health promotion programme that addresses diverse mental health aspects should be included in comprehensive workplace health promotion programmes. The selected sugar mill company in Swaziland does not address mental health or mental illness issues through a dedicated programme as part of the comprehensive workplace health promotion programme. Employees/workers with mental health and personal problems are referred to the Employee Assistance Programme (EAP) for assistance and help. Purpose and objectives of the study: The overall purpose of this study was to investigate and describe the mental health promotion needs and mental health concerns of factory workers at a Sugar Mill Company in Swaziland. Research design and method: This study used a qualitative approach, descriptive in nature. In-depth face to face interviews using an interview guide was used to determine the mental health promotion needs of sugar factory workers. Through purposive sampled 20 workers participated in the study. Data analysis: Audio-taped interviews were transcribed verbatim and data were then analysed by means of themes, categories, and sub-categories using Tesch’s method. Main findings: Factors that influenced mental health negatively (stressors) were related to workplace factors (money, workload and long hours) and family factors (family needs money). The mental health promotion needs identified in relation to the workplace consisted of more opportunities for employees’ development, salary increase and enhanced management and communication skills of supervisors and managers. In addition, health and life skills education, as well as more counseling services were identified as mental health needs. Conclusions: The identified mental health needs can be addressed through the Sugar Mill’s existing workplace health promotion programme. Key words: Mental health promotion, mental health, needs, factory workers.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirement for the degree Master of Science in Nursing (Course work) March 2017
Keywords: Mental Health